2016
DOI: 10.1002/mpr.1543
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis risk screening: Validation of the youth psychosis at‐risk questionnaire – brief in a community‐derived sample of adolescents

Abstract: There have been several attempts to identify individuals potentially at high risk for psychotic-spectrum disorders using brief screening measures. However, relatively few studies have tested the psychometric properties of the psychosis screening measures in representative samples of adolescents. The main purpose of the present study was to analyse the prevalence, factorial structure, measurement invariance across gender, and reliability of the Youth Psychosis At-Risk Questionnaire - Brief (YPARQ-B) in a commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
(120 reference statements)
1
13
0
Order By: Relevance
“…Previous studies with adolescents and young adults from both clinical and non-clinical populations have shown similar results to those found in this study. For instance, adolescents who reported psychotic-like experiences indicated a wide range of mental health problems, such as depressive symptoms, emotional and behavioral problems [27,64]. These results have potential implications.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies with adolescents and young adults from both clinical and non-clinical populations have shown similar results to those found in this study. For instance, adolescents who reported psychotic-like experiences indicated a wide range of mental health problems, such as depressive symptoms, emotional and behavioral problems [27,64]. These results have potential implications.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in order to improve our prevention capacity, we need to incorporate known risk factors within (e.g., schizotypy, PLEs) and between multiple levels of analysis (e.g., genetic, psychophysiological, cognitive, psychopathological, demographic). In addition, adolescents with psychosis liability (e.g., higher scores on schizotypy/schizotypal measures) reported a higher prevalence of mental disorders, as well as psychopathology symptoms related to depression, anxiety, and suicidal behaviors, among others [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in adolescent and young adults from both clinical and nonclinical populations have shown similar results to those found in this study. For instance, adolescents who reported PLEs, indicated a wide range of mental health problems, such as depressive symptoms (Armando et al, ; Fonseca‐Pedrero, Paino, Lemos‐Giráldez, & Muñiz, ), emotional and behavioral problems (Fonseca‐Pedrero et al, ; Wigman et al, ), and suicidal behavior (ideation and attempts; Kelleher et al, ; Kelleher, Cederlöf, & Lichtenstein, ). To date, however, few studies have demonstrated the relationship between PLEs and bipolar‐like experiences at a subclinical level in nonclinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…PLEs are relatively common during adolescence, with the mean annual prevalence among adolescents aged 13 to 18 around 7.5% (Kelleher et al, ). In addition, adolescents with PLEs reported a high prevalence of mental Axis I diagnoses and psychopathology symptoms (e.g., depression, anxiety, bullying, and suicide attempts and ideation; Fonseca Pedrero & Debbané, ; Fonseca‐Pedrero et al, ; Kelleher et al, , ; Strauss, Raugh, Mittal, Gibb, & Coles, ) as well as social impairments, neurocognitive deficits, and structural brain abnormalities (Calkins et al, ; Satterthwaite et al, ). These findings converge to suggest that subclinical expression of psychosis phenotype may be useful in the understanding of the pathogenesis of psychosis as well as for the early identification of adolescents potentially at risk for psychotic spectrum before reaching clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We carried out a systematic search of all published literature between 2000 and 2016 on the prevalence of PE in children and adolescents (Appendix S1, Supporting information). A total of 25 studies met our inclusion criteria, and were divided into groups based on age and method of assessment (Barragan, Laurens, Navarro, & Obiols, ; Bartels‐Velthuis, Jenner, van de Willige, van Os, & Wiersma, ; De Loore et al, ; Dhossche, Ferdinand, Van der Ende, Hofstra, & Verhulst, ; Fonseca‐Pedrero et al, ; Fonseca‐Pedrero et al, ; Horwood et al, ; Jeppesen et al, ; Kelleher, Harley, Murtagh, & Cannon, ; Kelleher, Keeley, et al, ; Kinoshita et al, ; Kobayashi et al, ; Lataster et al, ; Laurens et al, ; Laurens, Hobbs, Sunderland, Green, & Mould, ; Nishida et al, ; Nishida et al, ; Polanczyk et al, ; Poulton et al, ; Roddy et al, ; Scott et al, ; Sun et al, ; van der Hoorn et al, ; Wigman et al, ; Yung et al, ). All of the studies reported the frequencies of either self‐reported PE (PE‐S), interview‐based measures of PE (PE‐I) or both, but only one paper reported results regarding the concurrence of PE‐S and PE‐I.…”
Section: Introductionmentioning
confidence: 99%